Sirtuin‐1/Mitochondrial Ribosomal Protein S5 Axis Enhances the Metabolic Flexibility of Liver Cancer Stem Cells. Issue 4 (26th June 2019) - Wei, Zhihao; Jia, Jiankun; Heng, Gang; Xu, Huailong; Shan, Juanjuan; Wang, Guiqin; Liu, Chungang; Xia, Jianyu; Zhou, Haijun; Wu, Min; Yang, Zhi; Wang, Meiling; et al.
Abstract : Metabolic reprogramming endows cancer cells with the ability to adjust metabolic pathways to support heterogeneously biological processes. However, it is not known how the reprogrammed activities are implemented during differentiation of cancer stem cells (CSCs). In this study, we demonstrated that liver CSCs relied on the enhanced mitochondrial function to maintain stemness properties, which is different from aerobic glycolysis playing main roles in the differentiated non‐CSCs. We found that liver CSCs exhibit increased mitochondrial respiratory capacity and that complex‐I of mitochondria was necessary for stemness properties of liver CSCs through regulation of mitochondrial respiration. Bioinformatics analysis reveals that mitochondrial ribosomal protein S5 (MRPS5) is closely related with the function of complex‐I. Further experiments confirmed that MRPS5 promoted the production of nicotinamide adenine dinucleotide (NAD + ), which is necessary for enhanced mitochondrial function in liver CSCs. MRPS5 played a critical role for liver CSCs to maintain stemness properties and to participate in tumor progression. Mechanistically, the acetylation status of MRPS5 is directly regulated by NAD + dependent deacetylase sirtuin‐1 (SIRT1), which is abundant in liver CSCs and decreased during differentiation. Deacetylated MRPS5 locates in mitochondria to promote the function complex‐I and the generation of NAD + to enhance mitochondrial respiration. Conversely, the acetylated MRPS5 gathered in nuclei leads to increased expression of glycolytic proteins and promotion of the Warburg Effect. Therefore, liver CSCs transform mitochondrial‐dependent energy supply to a Warburg phenotype by the dual function of MRPS5. Clinical analysis of SIRT1 and MRPS5 expression in tumor tissues showed the SIRT1 High /Cytoplasmic‐MRPS5 High profile was associated with patients with hepatocellular carcinoma with poor prognosis. Conclusion: SIRT1/MRPS5 axis participates in metabolic reprogramming to facilitate tumor progression and may serve as a promising therapeutic target of liver cancer.